KOLABORASI INTERPROFESIONAL APOTEKER DAN DOKTER PADA PENDERITA HIPERTENSI DI PUSKESMAS KOTA SEMARANG BERDASARKAN PERSPEKTIF APOTEKER - Gloria, Fransisca; Ana Auleina, Revly; Rizki Al Farizi, Gilang (Universitas Pekalongan, 2025)
The abstract in this section is written in English. Abstract consists of 200-500 words. typed in English and Bahasa Indonesia with 200-500 words in 1 column with 11pt font 1.0 spacing. Briefly explain backgrounds, objectives, methods, results and conclusion. Background : Interprofessional collaboration is a process of communication and joint decision-making with the aim of achieving successful patient therapy by respecting each other and the abilities of each health worker. Each health profession must be connected in one direction to achieve the same vision and must understand each other's roles and work tasks so that they can optimize clinical outcomes in treating chronic diseases. One of the diseases that requires effective and optimal collaboration between pharmacists and doctors is hypertension. This is because hypertension is one of the diseases with very high mortality and morbidity rates in the world. Objective : This study aims to see the picture of interprofessional collaboration between pharmacists and doctors in handling hypertension patients at Semarang City Health Centers. Method : This study was conducted through an observational approach with a cross-sectional design in the period June - July 2022 using the Collaborative Working Relationship (CWR) model. The population in this study were all pharmacists and doctors, each numbering 33 people who work at the Semarang City Health Center with a total of 33 Health Centers. The data analysis used in this study was descriptive univariate. Result : Based on the results of the study, the gender of the 33 pharmacist respondents was all female (100%), most respondents (51.5%) were 25-30 years old, and respondents were 41-55 years old (30.3%), the average level of education of respondents was S1+Profession (100%) and the length of work of some was 1-5 years (60.6%). In the trust domain, moderate results were obtained, the role specification domain obtained sufficient results, the initiation relationship domain obtained moderate results and in collaboration, quite effective results were obtained. Conclusion : Based on the trust domain, pharmacists have moderate trust in doctors, pharmacists have sufficient role specification towards doctors, pharmacists have moderate initiation relationships, and pharmacists' collaborative practices are quite effective towards doctors.